Nivel socio afectivo y su vinculación en los procesos adaptativos de niños con discapacidad intelectual moderada - Jumbo Espinoza, Kelly Jazmín; Morocho López, Jéssica Patricia (Machala, 2021)
The term intellectual disability began to be present in the 5th edition of the American Association for Mental Deficiency (AAMD) revealing a group of impairments and limitations of intellectual functioning as well as adaptive behavior in the conceptual, social and practical domains; in such a way that today it is the notion of a low standard of care in the socio-affective processes of children and adolescents with ID. From a theoretical point of view, intellectual disability is approached from different postulates, in essence the analysis of this research could be polarized around the attachment theory understood from a conceptualization as an affective bond that the human being generates with others in order to convey and express your emotions. Based on the above, In the present work, the following content of the analysis category has been determined: intellectual disability and adaptive processes: adaptive behavior, affectivity and individuality. These categories allowed the obtaining of relevant data on the linkage of the socio-affective level in the adaptive processes, from the case study of children with moderate intellectual disabilities in the City of Machala from a specialized educational context. The study was based on a qualitative paradigm with an analytical-descriptive method composed of a non-experimental design where it is observed These categories allowed the obtaining of relevant data on the linkage of the socio-affective level in the adaptive processes, from the case study of children with moderate intellectual disabilities in the City of Machala from a specialized educational context. The study was based on a qualitative paradigm with an analytical-descriptive method composed of a non-experimental design where it is observed These categories allowed the obtaining of relevant data on the linkage of the socio-affective level in the adaptive processes, from the case study of children with moderate intellectual disabilities in the City of Machala from a specialized educational context. The study was based on a qualitative paradigm with an analytical-descriptive method composed of a non-experimental design where it is observed the link and the level of influence that exists in the variables, observation, interviews with teachers, parents and a psychometric test were used as information collection techniques, as well as the KidsLife scale of Schalock and Executioner, based on the multidimensional evaluation of the quality of life, with the eight-dimensional model: social inclusion, self-determination, emotional well-being, physical well-being, material well-being, rights, personal development, interpersonal relationships; Likewise, the Family Questionnaire FF SI was applied, revealing the contribution on the degree of functionality of the family from 7 dimensions. The results indicate that there are high levels of difficulty in relating and forming socio-affective bonds in daily practice, derived from a contrast between the excess and lack of affectivity of 2 family models: semi-functional and non-functional. Thus, social interaction is decisive to avoid behavioral disorders and the production of positive relationships, socialization agents such as family, society, school and means of interaction support the development of learning and self-concept of children with ID; who internalize their emotions under the influence they generate and, in most cases, they are seen as complaints or somatic symptoms. Indeed, it is important to supervise and individualized attention through the application of psychopedagogical programs and specialized support to respond to personal satisfaction, reduce rejection ties where affectivity predominates without conditions. Consequently, it is concluded that the socio-affective level of children with ID generated by the context influences the degree of participation in the practice of values, abilities and skills in a responsible way, which requires stability in the demands of the environment and flexible planning before the changes
El término discapacidad intelectual comenzó a estar presente en la 5ª edición de la Asociación Americana de Deficiencia Mental (AAMD) develando un grupo de afectaciones y limitaciones del funcionamiento intelectual como también del comportamiento adaptativo en los dominios conceptual, social y práctico; de tal forma que hoy en la actualidad es noción de un bajo estándar de atención en los procesos socioafectivos de niños, niñas y adolescentes con DI. Desde un punto de vista teórico, la discapacidad intelectual es abordada desde diferentes postulados, en esencia el análisis de esta investigación se pudo polarizar entorno a la teoría del apego entendida desde una conceptualización como vínculo afectivo que el ser humano genera con los demás a fin de transmitir y expresar sus emociones. Con base en lo anterior, en el presente trabajo se ha determinado el siguiente contenido de categoría de análisis: la discapacidad intelectual y los procesos adaptativos: conducta adaptativa, afectividad e individualidad. Estas categorías permitieron la obtención de datos relevantes sobre la vinculación del nivel socioafectivo en los procesos adaptativos, a partir del estudio de caso de niños con discapacidad intelectual moderada de la Ciudad de Machala desde un contexto educativo especializado. El estudio se basó en un paradigma cualitativo con método analítico-descriptivo compuesto por un diseño no experimental en donde se observa el vínculo y el nivel de influencia que existe en las variables, se emplearon como técnicas de recolección de información la observación, entrevistas a docentes, padres de familia y prueba psicométrica, también la escala KidsLife de Schalock y Verdugo, basada en la evaluación multidimensional de la calidad de vida, con el modelo de ocho dimensiones: inclusión social, autodeterminación, bienestar emocional, bienestar físico, bienestar material, derechos, desarrollo personal, relaciones interpersonales; asimismo se aplicó el Cuestionario familiar FF SI, relevando el aporte sobre el grado de funcionalidad de la familia desde 7 dimensiones. Los resultados indican que existen niveles altos de dificultad para relacionarse y formar vínculos socioafectivos en la práctica diaria, derivados desde una contraposición entre el exceso y falta de afectividad de 2 modelos de familia: semifuncional y no funcional. Así pues, la interacción social es determinante para evitar trastornos de comportamiento y la producción de relaciones positivas, los agentes de socialización como la familia, sociedad, escuela y medios de interacción solventan el desarrollo de aprendizaje y autoconcepto de niños con DI; quienes interiorizan sus emociones bajo la influencia que estos generan y en la mayoría de casos se observan como quejas o síntomas somáticos. En efecto, es importante la supervisión y atención individualizada a través de la aplicación de programas psicopedagógicos y apoyo especializado para dar respuesta a la satisfacción personal, disminuir lazos de rechazo donde predomine afectividad sin condiciones. Por consiguiente, se concluye que el nivel socioafectivo de niños con DI generado por el contexto influye al grado de participación en la práctica de valores, habilidades y destrezas de forma responsable por lo que se requiere una estabilidad en las demandas del entorno y planificación flexible antes los cambios, con base en las preferencias y prioridades del sujeto para permitirles potenciar sus necesidades básicas y desempeñar una convivencia plena
Keywords: DISCAPACIDAD INTELECTUAL; HABILIDAD ADAPTATIVA EMOCION; AFECTIVIDAD; AUTONOMIA